Sexperiment : 7 days to lasting intimacy with your spouse - Young, Ed, 1961-; Young, Lisa. (New York : FaithWords, 2012)
Presents advice from a Christian perspective on maintaining a healthy sex relationship within marriage, discussing some of the obstacles to sexuality and what can be done to achieve a balance between everyday demands and marital sex.
Days of sex -- Stop making sexcuses ... and start making love -- The math of marriage -- It's time to get naked -- Looking out for number one -- Leaving lust Vegas -- Trust funds are nothing -- Pillow talk -- Boom chicka wah-wah (and other lessons from the R & B industry) -- The real big "O."
Includes bibliographical references.
Keywords: Sex in marriage -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity; Marriage -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity; Sex -- Religious aspects -- Christianity